CARDIOVASCULAR AUTONOMIC NEUROPATHY IN PATIENTS WITH DIABETES MELLITUS - NAZEEMA KHATOON; B. SANTHOSH KUMAR; MOHAMMED ABDUL HANNAN HAZARI (International Journal of Pharma and Bio Sciences, 2010)
The cardioautonomic reflexes of 82 diabetic subjects and 40 age and sex matched healthy controls were studied using blood pressure and heart rate variation in response to standing, deep breathing, isometric exercise, cold pressor test and determination of QTc interval. Among the 82 patients, 68 patients were found to have cardiac autonomic neuropathy (CAN). Results showed that diabetics had significantly impaired cardioautonomic reflexes compared to non-diabetics, which increases with the duration of diabetes. Out of 68 patients with CAN, QTc prolongation was observed in 64 patients. In conclusion the autonomic nervous system integrity is appeared to be greatly affected by diabetes mellitus and the degree of impairment was dependent on duration of the disease.